Indonesian Learning Model Training For Elementary School Teacher - Agus Hamdani; Zainah Asmaniah; Iin Indriyani; Muhammad Fahhmi Saepuloh; Suhartati Suhartati (Indonesian Journal of Community Empowerment (IJCE), 2021)
Abstract One of the indicators of student success in learning is the use of interesting and varied learning methods. Therefore, teachers must learn and improve their abilities regarding the selection and use of learning methods. In this regard, a training on the development and use of the Indonesian language learning model was held for school teachers. The training technique is carried out in three stages, namely, introduction, design, and simulation. Meanwhile, the learning models given are Firing Line, Make a Match, Window Shopping, and Number Head Together learning models. The number of participants who attended and the high enthusiasm of participants during the training proved that this training activity provided benefits for elementary school teachers to develop their abilities, especially in the selection and use of learning methods. Abstrak Keberhasilan siswa dalam pembelajaran salah satu indikatornya adalah penggunaan metode pembelajaran yang menarik dan bervariatif. Oleh karena itu, guru harus mempelajari dan meningkatkan kemampuannya terkait pemilihan dan penggunaan metode pembelajaran. Berkenaan dengan hal tersebut, maka diadakan sebuah pelatihan pengembangan dan penggunaan model pembelajaran bahasa Indonesia bagi guru sekolah. Teknik pelatihan dilaksanakan dengan tiga tahapan, yaitu, pengenalan, rancangan, dan simulasi. Sedangkan, model-model pembelajaran yang diberikan adalah model pembelajaran Firing Line, Make a Match, Window Shoping, dan Number Head Together. Banyaknya peserta yang hadir dan antusias peserta yang tinggi saat mengikuti pelatihan membuktikan, bahwa kegiatan pelatihan ini memberikan manfaat bagi guru sekolah dasar untuk mengembangkan kemampuan dirinya terutama dalam pemilihan dan penggunaan metode pembelajaran.